Tactile selective attention and body posture: assessing the multisensory contributions of vision and proprioception. - Soto-Faraco, S; Ronald, A; Spence, C (2004)
This study addressed the role of proprioceptive and visual cues to body posture during the deployment of tactile spatial attention. Participants made speeded elevation judgments (up vs. down) to vibrotactile targets presented to the finger or thumb of either hand, while attempting to ignore vibrotactile distractors presented to the opposite hand. The first two experiments established the validity of this paradigm and showed that congruency effects were stronger when the target hand was uncertain (Experiment 1) than when it was certain (Experiment 2). Varying the orientation of the hands revealed that these congruency effects were determined by the position of the target and distractor in external space, and not by the particular skin sites stimulated (Experiment 3). Congruency effects increased as the hands were brought closer together in the dark (Experiment 4), demonstrating the role of proprioceptive input in modulating tactile selective attention. This spatial modulation was also demonstrated when a mirror was used to alter the visually perceived separation between the hands (Experiment 5). These results suggest that tactile, spatially selective attention can operate according to an abstract spatial frame of reference, which is significantly modulated by multisensory contributions from both proprioception and vision.